Shared decision making with black patients: A scoping review - Nada Mhaimeed (14779444) (2023)
Objective The purpose of this review is to explore the breadth of research conducted on SDM in the care of Black patients. Methods We conducted a scoping review following the methodological framework outlined by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist. We searched articles related to original research on SDM in the care of Black patients in October 2022 using PubMed, Embase, and Google Scholar databases. Articles of all study designs (quantitative and qualitative), published or translated into English, were included. A standardized data extraction form and thematic analysis were used to facilitate data extraction by two independent reviewers. Results After removal of duplicates and screening, 30 articles were included in the final analysis. Black patients and clinician were found to not share the same understanding of SDM, and patients highly valued SDM in their care. Interventions to improve SDM yielded mixed results to enhance intent, participation in SDM, as well as health outcomes. Decision aids were the most effective form of intervention to enhance SDM. The most common barrier to SDM was patient-clinician communication, and was exacerbated by racial discordance, clinician mistrust, past experiences, and paternalistic clinician-patient dynamics. Conclusions SDM has the potential to improve health outcomes in Black patients when implemented contextually within Black patients’ experiences and concerns. Significant barriers such as clinician mistrust exist, and the overall perception in the Black community is that SDM does not occur sufficiently. Barriers to SDM seem to be most pronounced when there is patient-clinician racial discordance. Several interventions aimed at improving SDM with Black patients have shown mixed results. Future studies should evaluate larger-scale interventions with longer follow-up. Practice implications Shared decision making (SDM) has been proposed as a useful tool for improving quality and equity in Black patients’ care. However, Black patients experience lower rates of SDM compared to other populations. SDM has the potential to improve health outcomes in Black patients when implemented contextually within Black patients’ experiences and concerns. Other Information Published in: Patient Education and Counseling License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.pec.2023.107646